Penerapan Teknologi Pemrograman Visual Lisp Untuk Meningkatkan Kompetensi Penggambaran Pada Autocad Bagi Para Guru SMK Se Kota Semarang Dan Sekitarnya - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Anwar Sukito Ardjo, Rofarsyam (Teknis, 2014)
AutoCAD® widely used as computered drawing and designing tools. AutoCAD® also have ability doing a calculation and then present the result as automation drawing technique. This will run by coding all of manual task in the form of program with Visual LISP language. The facility of editing and compiling for Visual LISP is attached in AutoCAD®. The Visual LISP code applicable to design and make drawing work of vehicle components as mass product. The hoisterous of assembling of car by student of Vocational Senior High School in Indonesia giving opportunity for himself to design the vehicle components. Visual LISP will short a design time, because calculations and drawings will automatically done. There is no materials content of Visual LISP programming in the Lesson Plan of Vocational Senior High School in Indonesia, so it is an opportunity to introduce to some of teacher of Vocational Senior High School in Semarang. The introduce of Visual LISP programming was conducted on 1st and 15th of June 2013, followed by 40 teachers as participants. Result of evaluation from participants was 67% expressing very agree and 33% expressing to agree that technology accepted represent matter newly; 33,3% expressing very agree and 55,4% expressing to agree if contents of Visual LISP programming continued for the others; dissimilar opportunity. Others most suggestion in order to be continued for the advanced contents of Visual LISP programming. Keywords: Visual LISP Programming, AutoCAD automation design and drawing technique.